THE INFLUENCE OF PARENTAL EDUCATION AND STUDENT LEARNING STYLES ON ENGLISH SPEAKING ABILITY - Faisal Faisal; Anggraini Anggraini (Sean Institute, 2023)
This research aims to determine the influence of parental education and student learning style on English speaking ability (Expose Facto on Easy English Course students). The research method used is the expose facto method. Samples of 75 students were selected randomly using a simple random technique. In this case, the research was continued with (2x2) parametric analysis, namely two-way analysis of variance (ANOVA). The research results show, there is a significant influence of parental education inability to speak English—students' English Course. The acquisition of the Sig value proves this. = 0.001 < 0.05. Moreover, Fcount = 11.574, significantly influences learning style and ability to speak English in English courses. The acquisition of the Sig value proves this. = 0.000 < 0.05 and Fcount = 9.180. There is an interaction between education and learning styles towards the ability to speak English Easy English Course. The acquisition of the Sig value proves this = 0.127 > 0.05 and Fcount = 2.131. It is known that parental education and independent learning styles influence students' English-speaking abilities, so teachers should pay attention to each student's level of education and learning style in learning English.